TRADISI GHATIB BEGHANYUT SEBUAH PERADABAN ISLAM PADA MASYARAKAT SIAK SRI INDRAPURA, RIAU - Roza, Ellya; Ayudia Pama, Sindi; Inayah Pama, Violeta; bin Nik Hasan, Nik Abdul Rakib (Universitas Darussalam Gontor, 2023)
This paper is the result of research that aims to reveal the ghatib beghanyut tradition carried out by the people of Siak Sri Indrapura as the implementation of Islamic civilization. Siak Sri Indrapura as a Malay 'palace country' has a religious cultural heritage from the Siak Kingdom, which is still practiced today. The implementation of ghatib beghanyut is led by the ulama and is carried out jointly between the community and the leadership. This paper is an exploratory field research to get data about ghatib beranyut while this type of research is descriptive qualitative. The data collection technique was through observation, interviews and documentation, after which a content analysis was carried out. The results of the study found that ghatib beghanyut is a ritual tradition carried out by the people of Siak Sri Indrapura to reject the calamities that befell the community and the village. Rejecting reinforcements is done by means of remembrance and prayer on a boat while drifting without being rowed to follow the flow of the river by involving the community and state leaders. Dhikr and prayers are guided by local clerics. Ghatib beghanyut is the pronunciation of the Siak Sri Indrapura community which comes from the word 'ratib berhanyut'. The ghatib beghanyut tradition can be said to be the implementation of Islamic civilization which has fused with the people of Siak Sri Indrapura as a Malay country. Malay identical to Islam is a statement that is inherent and formed in its religious traditions and culture so that it becomes an important part in the development of sharia tourism promotion in Siak Regency where the implementation of this tradition involves umara, ulama and the community. The procession is full of remembrance and prayer to Allah SWT so that the people of Siak Sri Indrapura are always in a religious nuance that builds Islamic cultural behavior including always praying, believing in Allah's grace, trying to avoid disease, and strengthening brotherhood and unity.